AN ANALYSIS OF SHERLY ANNAVITA ILLOCUTIONARY ACT VIDEO IN YOUTUBE CHANNEL - Friska Nadia Azhari; Anita Anggraeni (IKIP Siliwangi, 2023)
This research is an analysis of Sherly Annavita illocutionary speech acts on a video on her YouTube channel. The purpose of this study is to describe the types and functions of illocutionary speech acts expressed by Sherly Annavita on her YouTube channel. The author uses a qualitative descriptive method in this study. This research also describes the illocutionary speech acts that are the most widely used and the least used. The author collects the necessary data sources by observing a video of Sherly Annavita on her YouTube channel, then the author notes the important information that is obtained and puts it in written form. After the author makes observations and obtains the data, then the writer classifies the data based on the type of illocutionary speech act. In the results of this study the authors analyzed all types of illocutionary speech acts and in this study showed that there was five illocutionary speech acts used in Sherly Annavita video in her video, namely representative, directive, commissive, expressive, and declarative. From the research results, it can be concluded that Sherly Annavita uses 27 utterances with a representative percentage of 59.25%, directive 14.81%, commissive 14.81%, commissive 3.7%, and declarative 7.4%. The result of the percentage shows that the representative is the type of illocution that is most widely used, in other words, Sherly Annavita makes many statements so that someone is motivated to make changes. Keywords: YouTube; Pragmatic; Speech Act; Illocutionary